PENGEMBANGAN BAHAN AJAR IPA TERPADU TIPE CONNECTED PADA MATERI ENERGI - Astiti, Kadek Ayu; Engge, Betris Yasinta (Jurusan Fisika dan Pengajaran IPA, 2020)
AbstractIntegrated Science Learning is an implementation of the 2013 curriculum. With the implementation of integrated science learning, it is hoped that separate science materials, namely physics, chemistry and biology, can be taught in an integrated and comprehensive manner in one Integrated Science field of study. Based on the results of observations, Integrated Science learning has not been fully implemented because the textbook used does not show the integration between physics, chemistry and biology in one concept, especially in energy material. Therefore, a connected type of integrated science teaching material product development was carried out in energy material. The purpose of this research is to find out how to develop this teaching material and determine the feasibility of this teaching material.The development model carried out is a modification of the Dick and Carey development model in 4 stages: first; conduct needs analysis through observation and interviews, second; developing an assessment instrument in the form of a questionnaire as a reference for product feasibility, third; designing products by determining the subject matter and basic competencies related to them as well as developing products by displaying the characteristics of being connected, fourth; conduct due diligence by material experts and media experts. The type of data used is in the form of cumulative data, namely assessments, responses, and suggestions obtained from experts. The data collection instrument used was a questionnaire using the Likert scale assessment criteria with the highest score of 4 (four) and the lowest score of 1 (one).Based on expert judgment, this teaching material is undergoing a revision stage. The results of the feasibility test analysis by material experts show a percentage of 91.27% and media experts 85.24% with an average of 88.25%, this teaching material is declared suitable for use as an Integrated Science Module Based on Connected in Energy Materials for Class SMP / MTs VII.